Evaluating Radioprotective Effect of Hesperidin on Acute Radiation Damage in the Lung Tissue of Rats - Rezaeyan, A. (J Biomed Phys Eng, 2016)
BACKGROUND: Oxidative stress plays an important role in the pathogenesis and progression of γ-irradiation-induced cellular damage, Lung is a radiosensitive organ and its damage is a dose-limiting factor in radiotherapy. The administration of dietary antioxidants has been suggested to protect against the succeeding tissue damage. The present study aimed to evaluate the radioprotective efficacy of Hesperidin (HES) against γ-irradiation-induced tissue damage in the lung of male rats. MATERIALS AND METHODS: Thirty two rats were divided into four groups. Rats in Group 1 received PBS and underwent sham irradiation. Rats in Group 2 received HES and underwent sham irradiation. Rats in Group 3 received PBS and underwent γ-irradiation. Rats in Group 4 received HES and underwent γ-irradiation. These rats were exposed to γ-radiation 18 Gy using a single fraction cobalt-60 unit, and were administered HES (100 mg/kg/d, b.w, orally) for 7 days prior to irradiation. Rats in each group were sacrificed 24 hours after radiotherapy (RT) for the determination of superoxide dismutase (SOD), glutathione (GSH), malondialdehyde (MDA) and histopathological evaluations. RESULTS: Compared to group 1, the level of SOD and GSH significantly decreased and MDA level significantly increased in group 3 at 24 h following irradiation, (p=0.001, p<0.001, p=0.001), respectively. A statistically significant difference in all parameters was observed for rats in group 4 as compared to group 3 (p<0.05). Histopathological results 24 hours after RT showed that radiation has increased inflammation, lymphocyte, macrophage and neutrophil compared to group 1 ( p<0.0125). Oral administration of HES before RT significantly decreased macrophage and neutrophil when compared to group 3 (p<0.0125), but partly there was inflammation and lymphocyte that indicated there was no significant difference when compared to group 3 (p>0.0125). CONCLUSION: Oral administration of HES was found to offer protection against γ-irradiation- induced pulmonary damage and oxidative stress in rats, probably by exerting a protective effect against inflammatory disorders via its free radical scavenging and membrane stabilizing ability.